The Effect of Stress on Students' Motivation in Faculty of Economics, Manado State University - Stevianus X. Mentang; Marlyn T. Londa (Journal of International Conference Proceedings (JICP), 2019)
The aim of this study is to determine the level of students’ stress and motivation, and to analyze the effect of stress on students' motivation in Faculty of Economics, Manado State University. The populations in this study are all fourth semester students, who enrolled in Management Department in 2018-2019. The number of samples is 127 respondents with an error rate of 5%. This study use Depression Anxiety and Stress Scale 42 (DASS 42) questionnaire to measure stress and it uses Motivated Strategies of Learning Questionnaire (MSLQ) to measure students' learning motivation. The data are analyzed using simple linear regression with the help of SPSS statistical software. The results show that 42% of students experience moderate stress, 35% of them experience mild stress, 23% of them are normal. There is none who experience severe and very severe stress. Student with high learning motivation is 43%. Student with moderate motivation is 38%. The remaining 19% have low motivation. There is an effect of stress on motivation with sig = 0.002. The effect of the stress variable on the motivation variable can be seen from output B that is equal to 0.985. The coefficient of determination is 0.072. This means that stress affects motivation by 7.2%.